Characteristics of intestinal microflora involved insacral nerve stimulation affecting visceral hypersensitivity - He, Zhi (Int J Clin Exp Pathol, 2019)
Objective: This study was to investigate the effect of intestinal flora-intestinal-brain on the visceral sensitivity of normal rat and visceral hypersensitivity model rats, and to explore the effect of intestinal flora-intestinal-brain axis on visceral hypersensitivity in rats. Methods: Sixty SD male newborn rats were randomly divided into 4 groups according to the random number table: group A, group B, group C, and group D, with 15 rats in each group. 15 sterile SD newborn rats, numbered E group. Group A: normal model group; group B, group C, group D, group E, all used acetogen enema sensitization method to establish a visceral hypersensitivity model. Group C was given the vancomycin antibiotic before the model group and in group D sacral nerve stimulation (SNS) was given after modeling. At the end of the treatment period, the visceral sensitivity, intestinal flora expression, expression of NGF, TrKA, NF-κB, TRPV1, pTRPV1, IL-1β, IL-10, IL-22, TNF-α, 5-HT, and γ-GABA were measured in each group. Results: (1) The VMR values of the sterile rat model group were significantly different from those of the model group and the SNS stimulation model group (P<0.01). The VMR values of the antibiotic model group were statistically significant compared with the SNS stimulation model group (P<0.01). (2) There was no bacterial growth in the sterile rat model group. The expression levels of the four bacterial groups were significantly different between the antibiotic model group and the SNS stimulation model group (P<0.01). (3) The expression of NGF and TrKA in the SNS stimulation model was higher than that in the antibiotic model group (P<0.05). The expression of NF-κB and pTRPV1 was lower than that in the model group (P<0.05). The NGF, TrKA, NF-κB, and pTRPV1 were hardly expressed, which was significantly lower than the other groups (P<0.05). (4) There was no significant difference in the content of each index between the normal model group and the antibiotic model group (P > 0.05), IL-10 and 5-HT levels in the normal model group, the sterile rat model group, and the antibiotic model. There was no significant difference between the group and the sterile rat model group (P > 0.05). The difference was statistically significant (P<0.01). Conclusion: The neurotransmitter produced by the intestinal flora can bind to the receptor TrkA and the translocation channel TRPV1 of intestinal tissue and CNS tissue, causing intestinal sensitivity changes.